1995
DOI: 10.1093/bja/75.5.578
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of propofol and isoflurane anaesthesia on right ventricular function and shunt fraction during thoracic surgery

Abstract: I.v. anaesthetic agents, including propofol, have not been shown to inhibit hypoxic pulmonary vasoconstriction (HPV). This may encourage the use of propofol in thoracic surgery where one lung ventilation (OLV) is required. We have compared the effects of maintaining anaesthesia with either isoflurane or propofol infusion on right ventricular function and shunt fraction. We studied 10 patients who received isoflurane and 12 who received propofol. When OLV commenced there was a greater reduction in both mean car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0
4

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(60 citation statements)
references
References 10 publications
0
56
0
4
Order By: Relevance
“…13 The effect of anesthetic drugs on right-heart function has not been extensively studied and has yielded conflicting results. 14,15 Overall RV performance is the result of the sum of the functions of the lateral wall, the septum, and to some extent the participation of the LV. 5,[16][17][18] The longitudinal function of the free wall of the RV can be assessed using tissue Doppler echocardiography.…”
Section: Discussionmentioning
confidence: 99%
“…13 The effect of anesthetic drugs on right-heart function has not been extensively studied and has yielded conflicting results. 14,15 Overall RV performance is the result of the sum of the functions of the lateral wall, the septum, and to some extent the participation of the LV. 5,[16][17][18] The longitudinal function of the free wall of the RV can be assessed using tissue Doppler echocardiography.…”
Section: Discussionmentioning
confidence: 99%
“…Propofol sedation in patients with acute respiratory failure or neurological disease receiving critical care was found to decrease right ventricular contractility and this effect was reversed by dobutamine [54]. Interestingly, in a comparison study of propofol and isoflurane in patients undergoing one-lung ventilation, there was a greater reduction in the mean cardiac index and right ventricular ejection fraction with propofol, but propofol was not associated with a significant increase in shunt fraction, whereas isoflurane was associated with a three-fold increase in shunt fraction [55]. Fentanyl and sufentanil have minimal effects on pulmonary haemodynamics [56].…”
Section: Principles Of Anaesthetic Managementmentioning
confidence: 99%
“…Previous clinical studies have shown controversial results regarding oxygenation, shunt fraction and hemodynamic parameters during OLV. (24)(25)(26)(27) Van Keer et al (24) studied 10 patients who underwent thoracotomy. Anesthesia was maintained with continuous intravenous infusion of propofol (10 mg/kg/h).…”
Section: Discussionmentioning
confidence: 99%
“…This could be due to methodological differences, since the measurements during OLV were started before the opening of the chest. Kellow et al (25) studied patients undergoing thoracotomy and noticed a significant increase in cardiac index and shunt fraction during the change from TLV to OLV. However, the interpretation of the shunt fraction is limited because patients were ventilated with 50% nitrous oxide in oxygen and PaO2 was not assessed for.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation